Trade-offs in parasitoid resistance and competitive ability in Drosophila - Sidwell, Jeni (Jihočeská univerzita, 2022)
Trade-offs in fitness traits in Drosophila were studied in a laboratory environment. Fly and wasp lines originated from an ecological community in a tropical rainforest in Queensland, Australia and were established in České Budějovice. Experimental evolution was used to impose selective pressures on populations of flies to select for parasitoid resistance and competitive ability. The selection regimes were followed by two separate phenotyping experiments to measure the resulting phenotypic changes and impose novel conditions to the evolved flies in order to identify trade-offs.
Trade-offs in parasitoid resistance and competitive ability in Drosophila
Keywords: ecology; evolution; eco-evolutionary dynamics; trade-offs; fitness; Drosophila; ecology; evolution; eco-evolutionary dynamics; trade-offs; fitness; Drosophila